Review of the primordial approaches to ethnicity: Focus on Kenya - Ondigi, Evans Anyona (Research Journal in Advanced Humanities, 2021)
This study gives an overview of the primordial approaches to ethnicity. Generally, there are two main approaches to understanding ethnicity: primordial and constructivist. Even though it acknowledges the popularity of the latter approaches and the critique they bring forth, it argues that they are not enough to erase the usefulness of the former (primordial approaches). It strongly regards the primordial approaches as foundational with regard to explaining the essence of ethnicity or ethnic belongingness. This study however focuses on the following five main features of the primordial approaches: common ancestry; culture; language; landscape; and names. It lends credence to Atieno-Odhiambo (2002) and Kumaravadivelu’s (2008) argument that ethnic belongingness has always been a perduring phenomenon, and that there has always been a desire among most people to identify ethnically. Lastly, in giving prominence to the present-day Kenya – an east African country – it also argues that while there should always be (as have always been) accommodating towards other ethnicities, including intermarrying with them, we should be proud of our specific ethnic belongingness, celebrate ethnic diversity and resist attempts to lose ourselves to some sort of ‘imposed’ global homogeneity which is fashioned to undercut our ethnic grounding.